Potassium conductance of the squid giant axon is modulated by ATP. - Bezanilla, F (1986)
This communication reports a modulating effect of intracellular ATP on the steady-state and kinetic properties of the delayed rectifier of the giant axon of the squid. When internally dialyzed or perfused giant axons from Loligo plei or Loligo pealei are voltage clamped at -60 mV and washed free of ATP, the potassium current at 0 mV is decreased, and the time course of the potassium current is faster. Upon readmitting ATP, the potassium current for pulses to potentials more positive than -30 mV is increased by a factor of up to 2.5, while for pulses to potentials more negative than -30 mV, it is decreased. In the presence of ATP the turn-on of the time course of the potassium current is slower, but the turn-off of the time course is faster. The effect of ATP is only observed when magnesium ions are present in the internal medium; ADP or the nonhydrolyzable ATP analogue adenosine 5'-[beta, gamma-methylene]-triphosphate has no effect. When the holding potential is -70 mV, the conductance-voltage curve is shifted to more positive potentials by ATP, but the maximum conductance is only slightly increased. Most of the effects of ATP may be explained by a phosphorylation step that alters the voltage sensor of the activation and inactivation gates of the potassium channels shifting the voltage dependence of both processes to more depolarized potentials.